Increased Lipoprotein(a) Is an Important Risk Factor for Venous Thromboembolism in Childhood - Nowak-Göttl, Ulrike; Junker, Ralf; Hartmeier, Marion; Koch, Hans-Georg; Münchow, Nicole; Assmann, Gerd; von Eckardstein, Arnold (Circulation (New York, N.Y.), 1999)
Background —Serum levels of lipoprotein(a) [Lp(a)] are determined largely by genetic variation in the gene encoding for apolipoprotein(a) [apo(a)], the specific protein component of Lp(a) that is very homologous to plasminogen. High plasma levels of Lp(a) increase the risk for premature atherosclerotic vessel diseases. We investigated the little-characterized role of Lp(a) as a risk factor for venous thromboembolic diseases, alone and in conjunction with established thrombophilic risk factors of proteins regulating blood coagulation and fibrinolysis. Methods and Results —Serum levels of Lp(a) and lipids, protein C, protein S, and antithrombin, as well as the size of apo(a) isoforms and the presence of the factor V:Q 506 mutation, were determined in 186 consecutively admitted children from neonates to 18 years old with a history of venous thrombosis and in 186 age- and disease-matched control subjects. Children with a history of venous thrombosis had a significantly higher median Lp(a) level (19 versus 4.4 mg/dL) than control subjects. The risk for thromboembolic events in children with Lp(a) levels in the upper quartile, ie, >30 mg/dL, was 7.2 (95% CI, 3.7 to 14.5). The size of apo(a) isoforms was inversely related to Lp(a) levels and to the risk for thromboembolic events. Compared with the highest quartile of the apo(a) size distribution, the lowest quartile was associated with a risk of 8.2. In addition, multivariate statistical analysis gives evidence that the factor V:Q 506 mutation (OR/CI, 2.8/1.6 to 4.9), protein C (OR/CI, 6.5/2.1 to 19), and antithrombin deficiency (OR/CI, 10.4/1.2 to 90) were independent risk factors of childhood venous thrombosis. Coincidence of elevated Lp(a) with factor V:Q 506 mutation or deficiencies of protein C or antithrombin further increased the risk for thromboembolic events to 8.4. Conclusions —Lp(a) >30 mg/dL is a risk factor for venous thromboembolism in childhood. Lp(a) measurements should be included in the screening of causal factors in children with venous thromboembolic events.